ENVIRONMENTAL MANAGEMENT SYSTEMS CERTIFICATION - Miler-Virc, Aniko; Glusica, Zdravko (Journal of Economic Development, Environment and People, 2012)
ISO 14001 prescribes the requirements for a system, not environmental performance itself. Similarly, certification is of the management system itself, not environmental performance. An audit is not conducted to ascertain whether your flue gas emissions are less than X part per million nitrous oxide or that your wastewater effluent contains less that Y milligrams of bacteria per litre. Consequently, the procces of auditing the system for compliance to the standard entails checking to see that all of the necessary components of a functioning system are present and working properly. A company can have a complete and fully functional EMS as prescribed by ISO 14001 without being certified. As certification can add to the time and expense of EMS development, it is important for you to establish, in advance, whether certification is of net benefit to you. Although most companies that develop an EMS do in fact certify, there are cases where certification does not add immediate value. Certification is not always beneficial to small and medium sized companies. Certification is not always necessary for companies with one or two large clients with environmental demands who are satisfied that you have a functional EMS (second-party declaration). Whatever decision you make, it is important to remember that just as a driver′s licence does not automatically make you a good driver, ISO 14001 certification does not automatically make your company environmentally benign or ensure that you will continually improve environmental performance. The system is only as good as the people who operate it.